2020
DOI: 10.1007/s11356-020-10550-4
|View full text |Cite
|
Sign up to set email alerts
|

Florfenicol induces renal toxicity in chicks by promoting oxidative stress and apoptosis

Abstract: To explore the mechanism of renal toxicity induced by florfenicol (FFC), 120 chicks were randomly divided into 6 groups, 20 in each group. Except for the control group, different doses of FFC (0.15 g/L, 0.3 g/L, 0.6 g/L, 1.2 g/L, and 1.8 g/L) were added to drinking water in the other 5 groups. Five days later, blood was collected from the vein under the wing, and the complete kidneys were obtained as soon as possible, then tested the experimental indicators. The results showed that compared with control group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Te decrease in antioxidant defenses can lead to an increase in oxidative stress, and an increase in oxidative stress leads to a depletion of antioxidant defenses like SOD and GSH, and the production of MDA will increase. When the production rate of MDA exceeds the clearance rate of SOD, it will damage the kidney and afect renal function [32]. Our results confrmed that the amount of serum SOD and GSH was increased and MDA was decreased following the treatment of FST in a dose-dependent manner, which indicated that FST could reduce ROS levels and alleviate oxidative stress-induced kidney damage.…”
Section: Discussionsupporting
confidence: 55%
“…Te decrease in antioxidant defenses can lead to an increase in oxidative stress, and an increase in oxidative stress leads to a depletion of antioxidant defenses like SOD and GSH, and the production of MDA will increase. When the production rate of MDA exceeds the clearance rate of SOD, it will damage the kidney and afect renal function [32]. Our results confrmed that the amount of serum SOD and GSH was increased and MDA was decreased following the treatment of FST in a dose-dependent manner, which indicated that FST could reduce ROS levels and alleviate oxidative stress-induced kidney damage.…”
Section: Discussionsupporting
confidence: 55%
“…Shen et al (2015) studied the effect of SMP on boar sperm motility and found that frozen semen containing 0.4 mg/mL SMP could protect boar sperm from oxidative damage and improve sperm motility and litter size in artificial insemination of sows. As a novel broad-spectrum antibiotic for chloramphenicol in livestock, FFC could not only cause liver function damage but also lead to abnormal renal function, which may be caused by oxidative stress and abnormal renal cell apoptosis (Wang et al, 2021a;Wang et al, 2021b). Multiple studies have found that SMP has a protective effect on the kidney by reducing oxidative stress in the kidney, promoting drug metabolism enzymes and inhibiting apoptosis of renal tissue (Lu et al, 2022;Wang et al, 2022) Adding 1.5 g/kg SMP to weaned piglets significantly increased the ratio of ileum villus height to crypt depth, and changed the density and population of intestinal microflora, which improved the digestion and absorption ability of weaned piglets (Jiang et al, 2020).…”
Section: Other Significant Effectsmentioning
confidence: 99%
“…Once the kidneys of broilers are damaged by excessive FFC, their development will be seriously hindered ( Wang et al, 2022 ). Previous studies found that FFC caused oxidative stress response in kidneys of chicks by inhibiting the expression of related factors in Nrf2-ARE pathway, and increased the apoptotic rate of renal histocytes by upregulating the expression of pro-apoptotic factors ( Wang et al, 2021b ; Lu et al, 2022 ). However, the effects of FFC on broiler kidneys are multifaceted, and its mechanisms are not completely clear.…”
Section: Introductionmentioning
confidence: 96%